MOF-derived carbon coating on self-supported ZnCo2O4–ZnO nanorod arrays as high-performance anode for lithium-ion batteries - Gan, Qingmeng; Zhao, Kuangmin; Liu, Suqin; He, Zhen (Journal of materials science, 2017)
The C–ZnCo 2 O 4 –ZnO nanorod arrays (NRAs), which consist of MOF-derived carbon coating on ZnCo 2 O 4 –ZnO NRAs, are rational designed and synthesized via a facile template-based solution route on Ti foil and used as high-performance anode for lithium-ion batteries (LIBs). The uniform coated MOF-derived carbon layers on the ZnCo 2 O 4 –ZnO nanorods surface can serve as a conductive substrate as well as buffer layer to restrain volume expansion during charge–discharge process. When tested as anodes for LIBs, the C–ZnCo 2 O 4 –ZnO NRAs show high reversible capacity of 1318 mA h g −1 at 0.2 A g −1 after 150 charge–discharge cycles. Furthermore, C–ZnCo 2 O 4 –ZnO NRAs also exhibit brilliant rate performance of 886.2, 812.8, 732.2 and 580.6 mA h g −1 at 0.5, 1, 2 and 5 A g −1 , respectively. The outstanding lithium storage performance of C–ZnCo 2 O 4 –ZnO NRAs could be ascribed to the stimulated kinetics of ion diffusion and electron transport originated from the shortened lithium-ion diffusion pathway and improved electronic conductivity benefit from uniformly coating MOF-derived carbon.